2013
DOI: 10.1016/s2214-109x(13)70015-9
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors for noma disease: a 6-year, prospective, matched case-control study in Niger

Abstract: Gertrude Hirzel Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1
13

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 34 publications
1
83
1
13
Order By: Relevance
“…More precisely, acute noma seems to be characterized by the diminution of Capnocytophaga and Fusobacteria genera and by the increase of Prevotella genus. 15,36,37 Indeed, Prevotella intermedia was already reported in previous studies undertaken with classical cultures. 35 Prevotella intermedia is a well-known periodontal pathogen in adults, but it has been detected also in the primary dentition of small children.…”
Section: Noma Sequelaementioning
confidence: 65%
See 2 more Smart Citations
“…More precisely, acute noma seems to be characterized by the diminution of Capnocytophaga and Fusobacteria genera and by the increase of Prevotella genus. 15,36,37 Indeed, Prevotella intermedia was already reported in previous studies undertaken with classical cultures. 35 Prevotella intermedia is a well-known periodontal pathogen in adults, but it has been detected also in the primary dentition of small children.…”
Section: Noma Sequelaementioning
confidence: 65%
“…Various diseases have been described in association with noma, such as malaria, typhus, measles, chickenpox, tuberculosis, and HIV infection. 4,15,16 Measles and malaria are the most frequently reported illnesses that precede noma. 4,5,17 These diseases often occur during the weaning period and have serious immunosuppressive effects.…”
Section: Etiological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…and Firmicutes (particularly Peptococcaceae and Syntrophomonadaceae ) phyla. Given that noma lesions stay localized [24], we compared bacterial content of lesion sites to non-lesion sites in an attempt to describe intra-patient differences in microbiota composition (Figure 2: column N/Nn). Noticeably, a broader bacterial diversity is found in non-lesion sites of noma samples, particularly with groups such as Proteobacteria (including Lautropia , an oral taxon of the Burkholderiaceae family), Bacteroidetes (including Capnocytophaga spp.…”
Section: Resultsmentioning
confidence: 99%
“…This study further indicated that having a well as the main water source in comparison to other water sources such as a borehole, river or tap, was associated with having noma in the group aged 0-5 years. Well water has a high risk of contamination from nearby pit latrines or livestock, 46 and the consumption of contaminated well water is a risk factor for diarrhoea, 47 which in turn is an identified comorbidity for children with noma. 48 Vaccination coverage in all eligible children included in the study was low.…”
Section: Discussionmentioning
confidence: 99%